Patient with Jaundice, Dyspnea and Hyperferritinemia after COVID-19 - V. R. Grechishnikova; P. E. Tkachenko; M. S. Zharkova; T. P. Nekrasova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
The aim: to highlight the importance of considering hemophagocytic lymphohistiocytosis in patients with jaundice of unclear origin and systemic inflammatory manifestations after coronavirus infection.Key points. A 64-y.o. patient was admitted to the hospital with jaundice, pruritus, fatigue, weight loss. The complaints occurred 2 weeks after discharge from the hospital for treatment of patients with coronavirus infection. Laboratory tests revealed signs of hepatic insufficiency, markers of cholestasis and inflammation persisted in time. Upon instrumental examination no signs of hepatosplenomegaly, biliary tree changes, intra- and extrahepatic obstruction were found. S. aureus was identified in blood cultures, CT scan of the facial skull bones showcased the focus of infection in the area of the roots of teeth 2.4 and 2.5. Therefore, antibiotics were prescribed. Subsequently, the patient's condition was complicated by the development of two episodes of acute respiratory distress syndrome, which occurred during the withdrawal of glucocorticosteroid therapy. Liver biopsy was performed, morphological study revealed signs of “vanishing bile duct” syndrome, excessive activation of macrophages and hemosiderosis of sinusoidal cells. Identified lesions can be found in hemophagocytic lymphohistiocytosis (HLH), a life-threatening complication of coronavirus infection. Glucocorticosteroids therapy, transfusions of human immunoglobulin, albumin, and parenteral nutrition have led to patient's condition improvement.Conclusion. COVID-19 provokes the development of secondary HLH 10 times more often than other respiratory viral infections. The possibility of hemophagocytic syndrome development should be considered, including cases of overlap syndrome with sepsis, in patients with unresolved jaundice, hyperferritinemia after coronavirus infection. Routinely used scales and criteria for diagnosis of HLH (H-score, HLH 2004) in such cases lacks sensitivity, therefore, careful analysis of clinical picture and exclusion of other causes of jaundice are required.